Selegiline Ameliorates Depression-Like Behavior in Mice Lacking the CD157/BST1 Gene, a Risk Factor for Parkinson’s Disease - Kasai, Satoka; Yoshihara, Toru; Lopatina, Olga; Ishihara, Katsuhiko; Higashida, Haruhiro (Frontiers in Behavioral Neuroscience, 2017)
Parkinson’s disease (PD), a neurodegenerative disorder, is accompanied by various non-motor symptoms including depression and anxiety, which may precede the onset of motor symptoms. Selegiline is an irreversible monoamine oxidase-B (MAO-B) inhibitor, and is widely used in the treatment of PD and major depression. However, there are few reports about the effects of selegiline on non-motor symptoms in PD. The aim of this study was to explore the antidepressant and anxiolytic effects of selegiline, using CD157/BST1 knockout (CD157 KO) mouse, a PD-related genetic model displaying depression and anxiety, compared with other antiparkinsonian drugs and an antidepressant, and was to investigate the effects of selegiline on biochemical parameters in emotion-related brain regions. A single administration of selegiline (1‒10 mg/kg) dose-dependently reduced immobility time in the forced swimming test (FST) in CD157 KO mice, but not C57BL/6N wild-type mice. At 10 mg/kg, but not 3 mg/kg, selegiline significantly increased climbing time in CD157 KO mice. A single administration of the antiparkinsonian drugs pramipexole (a dopamine D2/D3 receptor agonist) or rasagiline (another MAO-B inhibitor), and repeated injections of a noradrenergic and specific serotonergic antidepressant, mirtazapine, also decreased immobility time, but did not increase climbing time, in CD157 KO mice. The antidepressant-like effects of 10 mg/kg selegiline were comparable to those of 10 mg/kg rasagiline, and tended to be stronger than those of 1 mg/kg rasagiline. After the FST, CD157 KO mice showed decreases in striatal and hippocampal serotonin content, cortical norepinephrine content, and plasma corticosterone concentration. A single administration of selegiline at 10 mg/kg returned striatal serotonin, cortical norepinephrine, and plasma corticosterone levels to those observed in wild-type mice. In the open field test, repeated administration of mirtazapine had anxiolytic effects, and selegiline nonsignificantly ameliorated anxiety-like behaviors in CD157 KO mice. In the social interaction and preference tests, repeated mirtazapine ameliorated the high anxiety and low sociability of CD157 KO mice, whereas selegiline did not. These results indicate that selegiline has antidepressant and mild anxiolytic effects in CD157 KO mice, and suggest that it is an effective antiparkinsonian drug for depressive and anxiety symptoms in PD patients with a CD157 single nucleotide polymorphism.